1 | initial version |

$Ax \leq b \iff Ax - b \leq 0 \iff (-A)x + b \geq 0.$

2 | No.2 Revision |

$Ax \leq b \iff Ax - b \leq 0 \iff (-A)x + b \geq 0.$

So if you have $(A, b)$ such that $Ax \leq b$ is your polyhedron, then use $(-A, b)$ as input to Sage's `Polyhedron`

.

3 | No.3 Revision |

$Ax \leq b \iff Ax - b \leq 0 \iff (-A)x + b \geq 0.$

So if you have $(A, b)$ such that $Ax \leq b$ is your polyhedron, then ~~use $(-A, ~~$(A', b)$ ~~as input to Sage's ~~where $A'=-A$ are such that $A'x + b \geq 0$ is also your polyhedron.`Polyhedron`

.

4 | No.4 Revision |

$Ax \leq b \iff Ax - b \leq 0 \iff (-A)x + b \geq 0.$

So if you have $(A, b)$ such that $Ax \leq b$ is your polyhedron, then $(A', b)$ where $A'=-A$ ~~are ~~is such that $A'x + b \geq 0$ is also your polyhedron.

5 | No.5 Revision |

$Ax \leq b \iff Ax - b \leq 0 \iff (-A)x + b \geq 0.$

So if you have $(A, b)$ such that $Ax \leq b$ is your polyhedron, then the pair $(A', ~~b)$ ~~b)$, where ~~$A'=-A$ ~~$A'=-A$, is such that $A'x + b \geq 0$ is also your polyhedron.

Copyright Sage, 2010. Some rights reserved under creative commons license. Content on this site is licensed under a Creative Commons Attribution Share Alike 3.0 license.